Analisis Beban Kerja Mental Menggunakan NASA-TLX pada Divisi Produksi Perusahaan Metal Stamping - Nadia Ayudya Adikarana; Dene Herwanto; Muhammad Rizal Rifa'i (Go-Integratif : Jurnal Teknik Sistem dan Industri, 2022)
Human resources as one of the company's assets must be considered because they affect the performance of the company. Metal stamping companies that apply the make to order and make to stock concepts in processing each of their products lead to a high number of requests that need to be achieved every day by workers. Workers have to work 8 and a half hour/day. The purpose of this study is to analyze the factors that affect the mental workload as well as the proposed improvements needed based on the working conditions of the workers. The method used is NASA-TLX, a subjective measurement method of mental workload. This method is in the form of a questionnaire which distributed to 10 workers in the Production Division. The results from this study indicate that the average WWL score is 61.07 and is in the high category. Then it is known factors that affecting are the high target demand each day, the rest time is quite low, the heat from the stamping process, the lack of training on the machines on the production floor. The proposals given are increasing rest periods, holding regular training, providing adequate facilities.